2015
DOI: 10.1002/adhm.201400591
|View full text |Cite
|
Sign up to set email alerts
|

Additively Manufactured Device for Dynamic Culture of Large Arrays of 3D Tissue Engineered Constructs

Abstract: The ability to test large arrays of cell and biomaterial combinations in 3D environments is still rather limited in the context of tissue engineering and regenerative medicine. This limitation can be generally addressed by employing highly automated and reproducible methodologies. This study reports on the development of a highly versatile and upscalable method based on additive manufacturing for the fabrication of arrays of scaffolds, which are enclosed into individualized perfusion chambers. Devices containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…Hence, we developed compression bioreactor system to study the effects of cyclic compressive strains on the maturation of engineered bone grafts. Studies have shown the development of array of scaled‐down, multi‐compartment bioreactor systems aid in acceleration of tissue characterization and also help to minimize experimental variations during parametric optimization . Our custom‐built, multi‐chamber compression bioreactor system can apply a range of strains on cellular scaffolds in a semi‐high‐throughput fashion with independent control of loading and medium conditions in each of the chambers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, we developed compression bioreactor system to study the effects of cyclic compressive strains on the maturation of engineered bone grafts. Studies have shown the development of array of scaled‐down, multi‐compartment bioreactor systems aid in acceleration of tissue characterization and also help to minimize experimental variations during parametric optimization . Our custom‐built, multi‐chamber compression bioreactor system can apply a range of strains on cellular scaffolds in a semi‐high‐throughput fashion with independent control of loading and medium conditions in each of the chambers.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown the development of array of scaled-down, multi-compartment bioreactor systems aid in acceleration of tissue characterization and also help to minimize experimental variations during parametric optimization. 45,46 Our custom-built, multichamber compression bioreactor system can apply a range of strains on cellular scaffolds in a semi-high-throughput fashion with independent control of loading and medium conditions in each of the chambers. In our study, we seeded MSCs on the scaffolds using fibrin glue which has been proven to facilitate high seeding density, good cellular retention, and robust osteogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The method consists of four main steps: (a) the injection of the fibrin components including the cells into the silicone tube, (b) the gelation process, (c) the ejection of the gel after polymerization and (d) the stretching of the resulting fiber. We expect that already existing solutions for automated pipetting, handling, collection, gripping of samples and controlled linear displacement could be assembled to create an ad‐hoc automated system for the production of the fibers in a sterile, closed environment (Bhuthalingam, Lim, Irvine, & Venkatraman, ; Bartolo, Domingos, Gloria, & Ciurana, ; P. F. Costa et al, ; Kikuchi et al, ; Mekhileri et al, ). A GMP conform production is facilitated by the limited number of parts in contact with the materials composing the fibers and the commercial availability of GMP‐conform cell‐work stations.…”
Section: Discussionmentioning
confidence: 99%
“…4). Removal of the scaffolds required breaking apart the outer chamber and would benefit from improved ease of access in future designs; however, a subsequent study did demonstrate the capability for the system to be scaled up with the simultaneous culture of 96 scaffolds (Costa et al, 2015). If fluid paths trace a tortuous, indirect path through the scaffold, the effective distance of mass transport is increased.…”
Section: Challenges Of Shapementioning
confidence: 99%